A probe into the developmental pattern of public art education in colleges and universities from the perspective of new media - Zhang, Kaile; Hsiao, Tsung-Chih; Tian, Qing (Frontiers in Psychology, 2023)
The integration of public art education and new media in colleges and universities remains a trend which cannot be stopped. As new media has had a beneficial impact on teaching content, forms of teaching, and teaching effects, it has also created various challenges for public art education in colleges and universities. While investigating the current state of integrating new media with public art education in colleges and universities, it was found that the impact of new media benefits more than it harms, whether it be online, in-person, theoretical, or practical teaching. Based on the current state, future policy focus, the direction of new media's changes, and the depth of cultural and art resources, new media and public art education in colleges and universities will continue to deepen integration and show further improvement. Using a survey of more than a dozen universities in the Jiangsu Province and the results of a questionnaire survey of 116 college students, this paper probes into the changes in public art education in colleges and universities in the new media era and explores the future developmental pattern of public art education in colleges and universities both internally and externally.